2005
DOI: 10.1111/j.0014-3820.2005.tb01822.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGEOGRAPHIC STRUCTURE OF THE FIRE ANTSOLENOPSIS INVICTAIN ITS NATIVE SOUTH AMERICAN RANGE: ROLES OF NATURAL BARRIERS AND HABITAT CONNECTIVITY

Abstract: Abstract. We generated mitochondrial DNA (mtDNA) sequence data from 402 individuals of the fire ant Solenopsis invicta collected from 11 native populations and analyzed these data using a combination of demographic, phylogenetic, and phylogeographic methods to infer features of the evolutionary history of this species. Prior expectations regarding high levels of genetic structure and isolation by distance among populations were supported by the data, but we also discovered several unanticipated patterns. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 65 publications
(90 reference statements)
6
36
0
Order By: Relevance
“…Secondly, Ahrens et al (2005) reported a sharp genetic discontinuity in the native distribution of fire ants along the border between Argentina and Brazil. In this region, a 2500 km-long geographical barrier to gene flow (the Mesopotamia wetlands) divides the distribution of fire ants into two evolutionary independent groups, one in the south-western portion of the range and the other in the north-eastern portion (Ahrens et al, 2005). Environments characteristic of the counties first invaded by fire ants occur primarily to the west of this division.…”
Section: Source Of Founding Propagulesmentioning
confidence: 68%
See 1 more Smart Citation
“…Secondly, Ahrens et al (2005) reported a sharp genetic discontinuity in the native distribution of fire ants along the border between Argentina and Brazil. In this region, a 2500 km-long geographical barrier to gene flow (the Mesopotamia wetlands) divides the distribution of fire ants into two evolutionary independent groups, one in the south-western portion of the range and the other in the north-eastern portion (Ahrens et al, 2005). Environments characteristic of the counties first invaded by fire ants occur primarily to the west of this division.…”
Section: Source Of Founding Propagulesmentioning
confidence: 68%
“…First, preliminary genetic analyses of native and invasive fire ant populations also suggest that the most likely source of individuals founding the US population is the southern half of the native range, and north-eastern Argentina in particular (Mescher et al, 2003). Secondly, Ahrens et al (2005) reported a sharp genetic discontinuity in the native distribution of fire ants along the border between Argentina and Brazil. In this region, a 2500 km-long geographical barrier to gene flow (the Mesopotamia wetlands) divides the distribution of fire ants into two evolutionary independent groups, one in the south-western portion of the range and the other in the north-eastern portion (Ahrens et al, 2005).…”
Section: Source Of Founding Propagulesmentioning
confidence: 99%
“…Avise (2009) pointed out that low dispersal species are characterized by strong genealogical structure, but emphasized that 'even in vagile species, historical barriers to dispersal can sometimes be insurmountable', promoting high population structure. Indeed, this pattern was also found in two species of ants with flying queens: Solenopsis invicta (Ahrens, Ross & Shoemaker, 2005) and Formica pratensis (Goropashnaya et al 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Polymerase chain reactions for the mtDNA included primers C1-J-2195 and DDS-COII-4 (Ross & Shoemaker 1997) designed to specifically amplify an approximately 910 bp fragment corresponding to portions of the cytochrome oxidase subunit I (cox-1) and subunit II (cox-2) genes. PCR reaction conditions and thermal cycling profile were identical to those described in Ahrens et al (2005). PCR products were purified and then used as templates for sequencing reactions performed using the two primers above and the ABI PRISM BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems, CA, USA).…”
Section: Mitochondrial Dna (Mtdna) Sequencingmentioning
confidence: 99%